Gender and Technology: A Reader - Lerman, Nina; Oldenziel, Ruth; Mohun, Arwen P. (Johns Hopkins University Press, 2003)
For most of human experience, certainly of late, the artifacts of technological civilization have become closely associated with gender, sometimes for physiological reasons (brassieres or condoms, for example) but more often because of social and cultural factors, both obvious and obscure. Because these stereotypes necessarily have economic, social, and political consequences, understanding how gender shapes the ways we view and use technology―and how technology shapes our concept of gender―has emerged as a matter of serious scholarly importance. Gender and Technology brings together leading historians of technology to explore this entwined and reciprocal relationship, focusing on the tools (cars, typewriters, computers, vibrators), industries (dressmaking, steam laundering, cigar making, meat packing) and places (factories, offices, homes) of North America between 1850 and 1950. Together, these essays reveal the ways in which technology and gender―far from being essential, immutable categories―develop historically as social constructions.Contributors: Patricia Cooper, University of Kentucky; Paul N. Edwards, University of Michigan; Wendy Gamber, Indiana University; Carolyn M. Goldstein, Lowell National Historical Park, Lowell, Massachusetts; Rebecca Herzig, Bates College; Roger Horowitz, Hagley Museum and Library, Wilmington, Delaware; Ronald R. Kline, Cornell University; Jennifer Light, Northwestern University; Rachel P. Maines, Cornell University's Hotel School Library; Judith A. McGaw; Joy Parr, Simon Fraser University.
Keywords: Business History and gender